Implementation of United Arab Emirates competency framework for medical education in undergraduate medical curriculum - Subhranshu Sekhar Kar; Rajani Dube; Biji Thomas George; Laxminarayana Kurady Bairy; Ali H. Hajeer; Ismail Ibrahim Ali Matalka (BMC Medical Education)
Abstract Background The dynamic and evolving demands of modern healthcare systems necessitate advancements in medical education. Competency-Based Medical Education (CBME) is an outcomes-driven approach that prioritizes measurable competencies over traditional time-based training. The United Arab Emirates Competency Framework for Medical Education (UCFME) was developed to standardize and elevate the quality of medical education across the UAE, aligning with global standards while addressing local healthcare needs. This study documents the implementation process of UCFME in undergraduate medical curricula (eventhough the outcomes are yet to be established), focusing on strategies, challenges, and lessons learned. Methods The UCFME was developed collaboratively by the Ministry of Education, the National Institute for Health Specialties, and academic stakeholders. A mixed-methods approach was employed, involving literature reviews, surveys, Delphi consensus, focus groups, and workshops. Key thematic roles and competencies were identified. The framework was mapped to international standards, including CanMEDS and ACGME, and integrated into the curriculum using Kotter’s 8-Step Change Model. To operationalize UCFME, a structured four-step model was employed for gradual integration, emphasizing milestones, supervisory levels, and diverse assessment methods to track learner progression. Milestones were defined using the Dreyfus model. After curriculum mapping and constructive alignment, competencies were mapped to the Qualifications Framework-Emirates to align with national educational benchmarks. Faculty were trained in CBME principles, and assessment methods were redesigned to include Entrustable Professional Activities (EPAs) and milestone-based evaluations. Pilot implementation and feedback guided refinements in each step. Results The RAK College of Medical Sciences successfully integrated UCFME’s 9 thematic roles, 9 core competencies, 85 enabling competencies and 14 EPAs into the undergraduate curriculum. Pilot studies demonstrated improvements in curriculum alignment, faculty engagement, and assessment reliability. Challenges included resistance to change, faculty training needs, cultural considerations and resource disparities. Faculty workshops and simulation-based training enhanced instructional capabilities. Enablers such as government support, technological infrastructure, and collaborative networks facilitated implementation. Students demonstrated progression in competence, with targeted EPAs achieved through formative and summative assessments. Conclusions The UCFME implementation represents a transformative step in undergraduate medical education, aligning national curricula with international best practices. Its strategic implementation underscores the importance of structured change management, faculty engagement, and competency-based assessment. This framework provides a replicable model for other institutions aiming to adopt CBME, fostering a competent and adaptable healthcare workforce.